Kajian Emotional Branding dan Budaya Etnik Sunda pada Restoran Tradisional Sunda (Studi Kasus: Restoran Sindang Reret dan Restoran Bumbu Desa) - Monica Hartanti; Imam Santosa; Alfonso Ronald Koapaha (Wimba : Jurnal Komunikasi Visual, 2012)
Emotional Branding is an incorporated four strategic key factors, such as relationship, sensory experience, imagination, and vision. These four key factors create a "dialogue" among one brand and its consumer which fulfill their needs as well as their desires. This research aim for a determination of the branding strategies used in two Sundanese restaurants. The analysis focused on the corporate identities from two Sundanese restaurants as well as their tangible and intangible identities that regarded to the Sundanese culture. Data were collected through several observations, evaluations, and interview completed through a Focus Group Discussion. Afterward, the data were compiled and analyzed through the theory of Emotional Branding and the study of Sundanese culture. Therefore, this research is considered as a Qualitative Descriptive Analysis research. The findings of this research show that the a corporate identities of these two restaurants has been using the Sundanese ethnic culture for a while till today. A local ethnic culture considered as one of the trends in the branding design which involve several parties (especially designers) to process the design components in such a way that the local ethnic culture is not turned into a merely "cosmetic" of brand identity. Through Emotional Branding, someone could make Sundanese's culinary as a lifestyle by promoting the authenticity of its tradition supported by the four factors that exist in Emotional Branding.